Using Prophylactic Antihemorrhagic Medications in Second-Trimester Surgical Abortions. Issue 4 (7th October 2022) - Fairchild, Kelly; Altinok, Morgan; Kram, Jessica J. F.; Heslin, Kayla; Montgomery, Michelle; Michelson, Elizabeth Dickson; Dorton, Benjamin
Abstract : Prophylactic antihemorrhagic medication use during second-trimester dilation and evacuation procedures was associated with lower operative hemorrhage and estimated blood loss. Abstract : We aimed to estimate the association of prophylactic antihemorrhagic medication use during dilation and evacuation (D&E) with operative hemorrhage and estimated blood loss (EBL). Records for all pregnant patients between 14 and less than 22 weeks of gestation who had a D&E procedure from January 2012 to December 2019 were retrospectively reviewed. Prophylactic antihemorrhagic medication use was defined as receiving vasoconstrictors, uterotonics, or both before identification of hemorrhage during a D&E procedure. Overall, 147 D&E procedures were completed at a mean of 16.4 (±2.2) weeks of gestation. Prophylactic medications were used in 72.1% (n=106) of D&E procedures. Prophylactic medication use was associated with lower operative hemorrhage (21.7% vs 51.2%, P <.01) and lower EBL (336.9 mL vs 551.3 mL, P <.01).